Geopolitical risks and financial stress in emerging economies - Tam NguyenHuu; Deniz Karaman Örsal (The World Economy, 2023)
We investigate the impacts of geopolitical risks (GPRs) on financial stress (FS) in major emerging economies from 1985 to 2019. Applying a recently developed panel quantile estimation method, we show that GPRs pose serious risks to the stability of the financial condition in emerging economies. Namely, when FS is already equal to or above average, GPRs intensify this instability to a remarkable degree. Nevertheless, GPRs do not ignite the stress when the financial situation is benign. In emerging economies, foreign exchange markets and, to a lesser extent, the banking industry and the debt market suffer more severe consequences of geopolitical tensions than the stock market. In contrast, advanced economies, represented by the Group of Seven (G7), have witnessed detrimental consequences of GPRs on their stock markets, but negligible effects on other parts of their financial systems.
Keywords: 330; banking sector; debt market; emerging economies; financial stress; foreign exchange market; geopolitical risks; stock market